Yield ratios for the isomeric pair 121m Te, 121m Te produced in 122 Sb (d,2n) 121 Te nuclear reaction - Jorge Nassif, Sonia (1962)
Fil: Jorge Nassif, Sonia Comisión Nacional de Energía Atómica; Argentina